Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the given problem, where [tex]\( f(x) = -3x \)[/tex], we need to calculate the value of [tex]\( f(x) \)[/tex] for different values of [tex]\( x \)[/tex]. Let's fill in the table step by step:
1. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = -3 \times (-2) = 6 \][/tex]
So, [tex]\( f(-2) = 6 \)[/tex].
2. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = -3 \times (-1) = 3 \][/tex]
So, [tex]\( f(-1) = 3 \)[/tex].
3. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = -3 \times 0 = 0 \][/tex]
So, [tex]\( f(0) = 0 \)[/tex].
4. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = -3 \times 1 = -3 \][/tex]
So, [tex]\( f(1) = -3 \)[/tex].
5. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = -3 \times 2 = -6 \][/tex]
So, [tex]\( f(2) = -6 \)[/tex].
Now let's fill in the table with these calculations:
[tex]\[ \begin{array}{|c|c|} \hline x & f(x) \\ \hline -2 & 6 \\ \hline -1 & 3 \\ \hline 0 & 0 \\ \hline 1 & -3 \\ \hline 2 & -6 \\ \hline \end{array} \][/tex]
This gives us the final values for [tex]\( f(x) \)[/tex] for each [tex]\( x \)[/tex] as follows:
- [tex]\( f(-2) = 6 \)[/tex]
- [tex]\( f(-1) = 3 \)[/tex]
- [tex]\( f(0) = 0 \)[/tex]
- [tex]\( f(1) = -3 \)[/tex]
- [tex]\( f(2) = -6 \)[/tex]
1. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = -3 \times (-2) = 6 \][/tex]
So, [tex]\( f(-2) = 6 \)[/tex].
2. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = -3 \times (-1) = 3 \][/tex]
So, [tex]\( f(-1) = 3 \)[/tex].
3. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = -3 \times 0 = 0 \][/tex]
So, [tex]\( f(0) = 0 \)[/tex].
4. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = -3 \times 1 = -3 \][/tex]
So, [tex]\( f(1) = -3 \)[/tex].
5. Calculate [tex]\( f(x) \)[/tex] for [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = -3 \times 2 = -6 \][/tex]
So, [tex]\( f(2) = -6 \)[/tex].
Now let's fill in the table with these calculations:
[tex]\[ \begin{array}{|c|c|} \hline x & f(x) \\ \hline -2 & 6 \\ \hline -1 & 3 \\ \hline 0 & 0 \\ \hline 1 & -3 \\ \hline 2 & -6 \\ \hline \end{array} \][/tex]
This gives us the final values for [tex]\( f(x) \)[/tex] for each [tex]\( x \)[/tex] as follows:
- [tex]\( f(-2) = 6 \)[/tex]
- [tex]\( f(-1) = 3 \)[/tex]
- [tex]\( f(0) = 0 \)[/tex]
- [tex]\( f(1) = -3 \)[/tex]
- [tex]\( f(2) = -6 \)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.